Islamic Character Values Based On Local Wisdom (Study On The Kulawi Tribe Community Of Sigi Regency, Kaili Tribe, Donggala Regency, And Pamona Tribe Kab. Poso) - Hairuddin Cikka (Departement of Mathematics Education, 2024)
The Kaili, Kulawi, Kaili and Pamona tribes still maintain traditions because traditions are still very functional in the social life of the people in the Kulawi, Kaili and Pamona tribes This is in line with the theory of cultural functionalism proposed by Malinowski and Radcliffe Brown, that a culture survives because it turns out to have certain functions for the community concerned. The functions possessed by the Saparan tradition include the function of bringing prosperity, the function of maintaining kinship ties, the function of maintaining bonds of solidarity and harmony of citizens, the function of entertainment, and the function of maintaining cultural heritage. Every tradition as a form of local wisdom in the Kulawi, Kaili and Pamona tribes has Islamic character values.